HTML5 2D game development - Geary, David M. 1957- (O'Reilly, 2013)
"Learn how to implement 2D video games, using the HTML5 Canvas element and HTML5's support for animations. This comprehensive 18-hour video covers every aspect of game development. You'll follow the development of a 2D HTML5 video game from start to finish that runs at a rock solid 60 frames per second on an iPad."--Resource description page.
Title from title screen (viewed Nov. 14, 2013). - Date of publication from resource description page (Safari, viewed Nov. 14, 2013)
Keywords: Video games -- Programming; Video games -- Design; HTML (Document markup language); Jeux vidéo; Programmation; Jeux vidéo; Conception; HTML (Langage de balisage); HTML; Computer games; Design; Video games; Programming; Electronic videos